Nail changes in systemic amyloidosis. Issue 8 (21st August 2021) - Litaiem, Noureddine; Chabchoub, Ines; Gara, Soumaya; Slouma, Maroua; Hamdi, Mohamed Salah; Zeglaoui, Faten
Abstract: Nail examination must be an essential part of physical examination in our daily clinical practice, as nail changes may be the revealing sign of systemic diseases in the absence of other alarming signs. Abstract : Nail examination must be an essential part of physical examination in our daily clinical practice, as nail changes may be the revealing sign of systemic diseases in the absence of other alarming signs.